Immunogenicity of a quadrivalent Ann Arbor strain live attenuated influenza vaccine delivered using a blow‐fill‐seal device in adults: a randomized, active‐controlled study1. Issue 6 (14th October 2012) - Sheldon, Eric A.; Jeanfreau, Robert; Sliman, Joseph A.; Charenkavanich, Supoat; Rousculp, Matthew D.; Dubovsky, Filip; Mallory, Raburn M.
<x xml:space="preserve">Abstract</x> Please cite this paper as: Sheldon et al. (2013) Immunogenicity of a quadrivalent Ann Arbor strain live attenuated influenza vaccine delivered using a blow‐fill‐seal device in adults: a randomized, active‐controlled study. Influenza and Other Respiratory Viruses 7(6), 1142–1150. Background Influenza B strains from two distinct lineages (Yamagata and Victoria) have cocirculated over recent years. Current seasonal vaccines contain a single B lineage resulting in frequent mismatches between the vaccine strain and the circulating strain. An Ann Arbor strain quadrivalent live attenuated influenza vaccine (Q/LAIV) containing B strains from both lineages is being developed to address this issue. Objectives The goal of this study was to evaluate whether Q/LAIV administered intranasally as a single dose to a single nostril, using a blow‐fill‐seal (BFS) delivery system had a similar immunogenicity and safety profile compared with the licensed trivalent vaccine delivered using the Accuspray device. Patients/Methods Adults aged 18–49 years were randomized to receive one intranasal dose of Q/LAIV delivered using a BFS device (Q/LAIV‐BFS; n = 1202) or one of two trivalent live attenuated influenza vaccines (T/LAIV) containing one of the corresponding B strains (total T/LAIV, n = 598). Primary endpoints were the post‐vaccination strain‐specific serum hemagglutination inhibition antibody geometric mean titers for each strain. Secondary immunogenicity endpoints, safety, and acceptability of the BFS device were also assessed. Results Q/LAIV was immunogenically non‐inferior to T/LAIV for all four influenza strains. Secondary immunogenicity outcomes were consistent with the primary endpoint. Solicited symptoms and AEs were comparable in both groups. Subjects considered the BFS device to be acceptable. Conclusions Immune responses to vaccination with Ann Arbor strain Q/LAIV‐BFS were non‐inferior to those with T/LAIV. Q/LAIV may confer broader protection against seasonal influenza B by targeting both major influenza B lineages.